Photoswitchable Microgels for Dynamic Macrophage Modulation. Issue 49 (2nd November 2022) - Kim, Yuri; Thangam, Ramar; Yoo, Jounghyun; Heo, Jeongyun; Park, Jung Yeon; Kang, Nayeon; Lee, Sungkyu; Yoon, Jiwon; Mun, Kwang Rok; Kang, Misun; Min, Sunhong; Kim, Seong Yeol; et al.
Abstract: Dynamic manipulation of supramolecular self‐assembled structures is achieved irreversibly or under non‐physiological conditions, thereby limiting their biomedical, environmental, and catalysis applicability. In this study, microgels composed of azobenzene derivatives stacked via π–cation and π–π interactions are developed that are electrostatically stabilized with Arg–Gly–Asp (RGD)‐bearing anionic polymers. Lateral swelling of RGD‐bearing microgels occurs via cis ‐azobenzene formation mediated by near‐infrared‐light‐upconverted ultraviolet light, which disrupts intermolecular interactions on the visible‐light‐absorbing upconversion‐nanoparticle‐coated materials. Real‐time imaging and molecular dynamics simulations demonstrate the deswelling of RGD‐bearing microgels via visible‐light‐mediated trans ‐azobenzene formation. Near‐infrared light can induce in situ swelling of RGD‐bearing microgels to increase RGD availability and trigger release of loaded interleukin‐4, which facilitates the adhesion structure assembly linked with pro‐regenerative polarization of host macrophages. In contrast, visible light can induce deswelling of RGD‐bearing microgels to decrease RGD availability that suppresses macrophage adhesion that yields pro‐inflammatory polarization. These microgels exhibit high stability and non‐toxicity. Versatile use of ligands and protein delivery can offer cytocompatible and photoswitchable manipulability of diverse host cells. Abstract : Remote control of microgels via tissue‐penetrative light is demonstrated. Near‐infrared‐light‐upconverted ultraviolet light stimulates in situ swelling of RGD‐bearing microgels that increases RGD availability, thereby facilitating macrophage adhesion linked with pro‐regenerative polarization. Visible light induces the deswelling of RGD‐bearing microgels that decreases RGD availability that suppresses macrophage adhesion that yields pro‐inflammatory polarization.